Divergence between confidence and knowledge of endodontists regarding non-odontogenic pain - Marcos Dezotti LUIZ; Letycia Accioly Simões COELHO; Rodrigo Ricci VIVAN; Marco Antônio Hungaro DUARTE; Murilo Priori ALCALDE; Paulo César Rodrigues CONTI; Yuri Martins COSTA; Leonardo Rigoldi BONJARDIM (University of São Paulo, 2023)
Abstract This study aimed to assess the self-reported levels of confidence and knowledge related to non-odontogenic pain among a group of Brazilian endodontists. Methodology A total of one hundred and forty-six endodontists affiliated with the Brazilian Society of Endodontics participated in the survey. The questionnaire, distributed via email or WhatsApp, contained inquiries designed to gauge self-perceived confidence and knowledge concerning non-odontogenic pain. The practitioners were categorized into four groups based on their self-reported familiarity with various orofacial pain types, classified as either sufficient or insufficient, and on their engagement in ongoing educational programs related to orofacial pain. Data were analyzed by Chi-Square Test and Fischer's exact test (p<0.05). Results Overall, self-reported confidence about non-odontogenic pain was high, especially for endodontists who considered their knowledge about orofacial pain sufficient, regardless of whether they had (71.1% - 97.8%) or not (35.7% - 96.4%) been continuously involved in education courses on orofacial pain. In general, self-reported knowledge about non-odontogenic pain was insufficient (0% - 42%), except in the question about how they would act in cases of pain that persists beyond the normal healing time after an endodontic procedure (70.6% - 81.9%). In general, endodontists are confident in their diagnosis and treatment of non-odontogenic pain. Nonetheless, this confidence did not correlate with a commensurate knowledge depth of. Thus, specialization courses in endodontics should highly consider training and qualifying these professionals in the diagnosis of non-odontogenic pain.